Persepsi Mahasiswa Program Studi Bimbingan dan Konseling terhadap Kompetensi Konselor di Lingkungan Pendidikan Inklusif - Marwan Maulana Yusuf; Tryastuti Irawati Belliny Manullang; Sunardi Sunardi; Ipah Saripah (Jurnal Pendidikan Kebutuhan Khusus, 2022)
Inclusive education is a way to support the diversity of students. Therefore, guidance and counselling teachers must have competence related to diversity issues. The purpose of this study was to determine student perceptions of the competence of counselors in an inclusive education environment. This research was conducted on 130 students of the Guidance and Counselling Study Program using a quantitative approach with a descriptive method with a questionnaire containing 30 questions via Google form. The results show: (1) Students' perceptions of the counsellor's professional competence were categorized as positive with an average score of 73%; (2) Students' perceptions of the counsellor's pedagogic competence were categorized as positive with an average score of 74%; (3) Students' perceptions of the counsellor's personality competence were categorized as positive with an average score of 74%; (4) Students' perceptions of the counsellor's social competence were categorized as positive with an average score of 72%; and (5) Overall, students' perceptions of counsellor competence were categorized as positive with an average score of 73%. This research was conducted only on Guidance and Counselling Study Program students through online questionnaires; therefore, the number of respondents and online collection could be taken into consideration when interpreting the data displayed.